GAMBARAN PERSEPSI WISATAWAN DOMESTIK MENGENAI KEAMANAN BERWISATA DI PANTAI MATAHARI TERBIT - Candra Putri, Luh Gede Agustini; Juniartha, I Gusti Ngurah; Suindrayasa, I Made (Coping: Community of Publishing in Nursing, 2024)
The number of deaths of domestic tourists due to beach accidents in Bali is still relatively high every year. The search results stated that there was a connection between three main factors, namely physical beach factors, facility factors and human factors, but no further investigation had been carried out regarding this matter. This is the background for the author to look for an overview of domestic tourists' perceptions regarding the safety of traveling to Matahari Terbit Beach. This research aims to determine the description of domestic tourists' perceptions of physical beach factors, facility factors and human factors at Matahari Terbit Beach. This type of research is descriptive quantitative research using survey methods. This research was carried out at Matahari Terbit Beach for 2 days, with a sample size of 171 people. The sampling technique uses a Purposive Sampling technique which is in accordance with the inclusion and exclusion criteria. Judging from the safety of traveling from physical beach factors, facility factors and human factors are all at moderate risk with a frequency of 131 people (76.6%), 153 people (89.5%) and 112 people (65.5%) respectively. With these findings, it is hoped that the Matahari Terbit Beach self-government can improve the safety of traveling on Matahari Terbit Beach, namely from the physical factors of the beach by increasing awareness to be aware of the times of high tide and low tide of sea water as well as the height of the waves and the strength of the currents around the beach, the facilities factor by how to understand the function of each security facility, and human factors by improving human behavior, knowledge and skills so that safety and security around the beach can be maintained.